EXPERIENCE OF PLACEMENT OF INDUSTRIAL ENTERPRISES IN FOREIGN COUNTRIES AND WAYS OF ITS USE (Academicia Globe: Inderscience Research, 2022)
The article shows the economic consequences of regulating industrial planning in the regions of foreign countries. In the regions, forms of industrial development and accommodation promotion are recognized, as well as programs aimed at their placement are covered.